(3JPcQI GHf GdYOjes - (3YeQ Hf CMeO Hf gHI Gddg Hf CHj LQGOI GdYbjdj, ceGd GdOjf GHf GdYOje,J (B660 (3g` s ((3HNW GdeDda s)
(3ChdgG (B:s
(3dYdi EHQGgje Hf YHO GdeMSf Hf bQfGU GdNRGYi GdMehi(B: (3Lafi dMHc bO LaGg gLhYg hGdbdH hGUdI Ydjc hdhYg s
(3BNQgG (B:s
(3eHJhQ hBNQ eG ajg PgH GddPjf jYGjT aiiCcaGfge hHbi GdPHf MjGJge dG JfaY bhe GPG GUfY GdfYGd NOhOge TcJ GdfYGd HGi PfH JUaY s
(3HgG SeGY Ydi Chd GdLRA GdNGeS YTQ SfI (B637(3g`s
(3hHBNQ GdfSNI eWGdYI dEHQGgje Hf MSjf GdJQLeGf SfI (B1011(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B275s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B170 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs